1989
DOI: 10.1111/j.1440-169x.1989.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Localization of Envelope Glycoproteins in Oocytes of Xenopus laevis using Immunocytochemical Methods

Abstract: Development Growth & DifferentiationThe site of origin and the mode of differentiation of the coelomic envelope (CE) in growing oocytes of Xenopus laevis were studied using the rabbit antiserum raised against the isolated envelope from oviposited eggs. The antiserum preabsorbed with egg extracts reacted with most components of CE glycoproteins detectable by SDS-PAGE, and stained specifically the CE of full-grown (st. VI) oocytes using indirect immunofluorescence methods. Transmission electron microscopy employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 27 publications
(17 reference statements)
1
26
0
Order By: Relevance
“…In most mammalian species including mice, there is clear evidence showing that ZP glycoproteins are synthesized by the growing oocytes (Bleil & Wassarman 1980). In X. laevis, they are also expressed in the oocytes (Yamaguchi et al 1989). In addition to the oocytes-restricted expression, the follicular granulosa cells also contribute to the synthesis of ZP3 in rabbits (Lee & Dunbar 1993) and in cynomolgus monkeys (Martinez et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In most mammalian species including mice, there is clear evidence showing that ZP glycoproteins are synthesized by the growing oocytes (Bleil & Wassarman 1980). In X. laevis, they are also expressed in the oocytes (Yamaguchi et al 1989). In addition to the oocytes-restricted expression, the follicular granulosa cells also contribute to the synthesis of ZP3 in rabbits (Lee & Dunbar 1993) and in cynomolgus monkeys (Martinez et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although no ZPD homolog has been identified in mammalian species, the expression of ZP glycoproteins appears to be regulated differently in different species. There is clear evidence showing that ZP3 is synthesized by the oocytes themselves in mice (Bleil & Wassarman 1980) and in Xenopus (Yamaguchi et al 1989), whereas the granulosa cells in the follicles also participate in the formation of ZP3 in rabbits (Lee & Dunbar 1993) and in cynomolgus monkeys (Martinez et al 1996). On the other hand, a glycoprotein homologous to ZP3 in chorion, the fish egg envelope, is produced in the liver and transported to the ovary by the blood circulation, like vitellogenin (Hamazaki et al 1985(Hamazaki et al , 1989.…”
Section: Discussionmentioning
confidence: 99%
“…However, TEM studies employing IgGconjugated colloidal gold revealed that vitelline envelope antigens were distributed throughout the whole cytoplasm and began to deposit around the surface of the stage I oocyte. 22 This study indicated that the cytoplasm of the stage I oocyte already contained components reactive with anti-vitelline coat antibodies 22 , thus suggesting that the oocyte may play a major role in synthesizing its own vitelline envelope.…”
Section: Disscussionmentioning
confidence: 86%